Functional Disability in Older Adults Maintained on Peritoneal Dialysis Therapy. Issue 1 (January 2016) - Ulutas, Ozkan; Farragher, Janine; Chiu, Ernest; Cook, Wendy L.; Jassal, Sarbjit V.
♦ Background: Older in-center hemodialysis patients have a high burden of functional disability. However, little is known about patients on home chronic peritoneal dialysis (PD). As patients opting for home dialysis are expected to play a greater role in their own dialysis care, we hypothesized that a relatively low number of PD patients would require help with basic self-care tasks (ADL) and instrumental activities of daily living (IADL). ♦ Methods: We used a cross-sectional study design to measure the proportion of patients aged 65 years and older undergoing outpatient PD who needed help with day-to-day activities. Patients living in nursing homes were excluded from the study. Functional dependence in ADL and IADL tasks were measured by the Barthel and Lawton Scales. Physical performance measures used included the timed up-and-go (TUG) test, chair stands and Folstein mini-mental score (MMSE). ♦Results: A total of 74 of 76 (97%) eligible PD patients participated. Patients had a mean age of 76.2 ± 7.5 years. Thirty-six percent had impaired MMSE scores, 69% were unable to stand from a chair without the use of their arms and 51% had abnormal TUG scores. Only 8 patients (11%) were fully independent for both ADL and IADL activities. Dependence in one or more ADL activity was reported by 64% of participants, while 89% reported dependence in one or more IADL. ♦Conclusions: Impaired physical and functional performance is common in older patients maintained on PD. Collaborative geriatric-renal programs may be beneficial within the dialysis community.